Mapping invasive species (Acacia dealbata Link) using ASTER/TERRA and LANDSAT 7 ETM+ imagery - Viana, Helder (2012)
The rapid spread of invasive alien species (IAS) is now recognised as one of the greatest threats to the ecological and economic well being of the planet. This study shows a comparison between ASTER/TERRA and ETM+/LANDSAT 7 sensors data suitability for mapping the Acacia dealbata Link spots. The work was carried out in central Portugal (Viseu region) where the presence of invader species in pure stands is quite significant. The images were ortho- rectified and submitted to supervised classifications techniques. The achieved results showed an overall accuracy of 89.42% over the ETM+ image and 86.69% over the ASTER image. For the class Acacia dealbata Link, the producer’s precision was 100% for both images but the user’s accuracy was only 23% in ETM+ and 12% in ASTER image. The obtained results suggest good perspectives for the use of this type of satellite images in order to detect and map this invasive species.